Characterization And Identification of Halophilic Bacteria (Rastrelliger sp.) Extracellular Lipase Generator in Beringharjo Market - Octavia, Bernadetta; Rakhmawati, Anna (Indonesian Journal of Bioscience (IJOBI), 2024)
Advances in biotechnology have allowed for the widespread use of lipase enzymes. One of the producers of lipase enzymes is halophilic bacteria. This study aims to determine the characteristics and genus, as well as the kinship relationship between lipase-producing halophilic bacterial isolates from salted fish (Rastrelliger sp.) in Beringharjo Market, Yogyakarta. Salted fish samples were isolated on Nutrient Agar + 3% NaCl + Tween 80 + 0.1% Rhodamine-B selective media to grow lipase-producing halophilic bacteria. Identification was carried out by the matching profile method based on Bergey's Manual of Determinative Bacteriology. The kinship relationship between bacterial isolates was classified using MVSP 3.1 software with the UPGMA clustering algorithm and constructed in the form of a dendogram.